Duration of anti-treponemal immunoglobulin M seroreversion after successful syphilis treatment in HIV-positive and -negative patients. (May 2021) - Paparizos, Vasilios; Tsimpidakis, Antonios; Nicolaidou, Electra; Daskalakis, Evangelos; Paparizou, Eleni; Vasalou, Varvara; Vrioni, Georgia; Rigopoulos, Dimitris
Treponemal immunoglobulin M (IgM) antibody detection is currently among serologic tests used for syphilis diagnosis. However, the exact role of these antibodies is unclear. In this retrospective study of 326 (198 HIV positive and 128 negative) patients with early syphilis and positive IgM serology, data were analysed to investigate the time of IgM seroreversion after treatment and correlation with covariate factors. Median time of IgM seroreversion in the study population was 9 months (range 3–84, interquartile range 5–12). No statistically significant difference was observed between HIV-positive and -negative patients. At 12 months, 80.1% of the patients had a negative IgM test. At 6 months, 100% of HIV-positive patients had a fourfold decrease or greater in Venereal Disease Research Laboratory titres, but only 35.4% had a negative treponemal IgM. Secondary and early latent stage patients had a slower seroreversion of IgM (Hazard Ratio (HR) = 0.73, p = 0.064 and HR = 0.60, p = 0.023, respectively) than those with primary syphilis. A very strong association was observed of time to seroreversion of treponemal IgM with baseline VDRL titre ( p < 0.001). Treponemal IgM antibody detection often cannot distinguish between active and successfully treated syphilis. Treponemal IgM may only be useful in the cases recommended in the guidelines, and in cases of untreated syphilis, it could support but not confirm the diagnosis.